Dermatofibrosarcoma protuberans of the hand in a young child: A case report and review of literature - Mohammed Amin Jameel; Kirtana S; Prithviraj Premkumar; Subalakshmi Balasubramanian; Jagadesh Chandra Bose; Arunan Murali; Latha M. Sneha (Pediatric Hematology Oncology Journal, 2023)
Background: Dermatofibrosarcoma protuberans is an infiltrating, intermediate grade neoplasm arising from dermis. It has a high rate of recurrence and low rates of metastasis. It is rare in childhood and is commonly observed in trunk and extremities. Due to the rarity of the tumor and non-characteristic findings, diagnosis of dermatofibrosarcoma protuberans is often missed in young children. Surgical excision is the treatment of choice and has excellent prognosis. Case report: We report a case of dermatofibrosarcoma protuberans in a 4-year-old, who had presented with a nodular lesion in the dorsum of right hand. It was initially managed as vascular lesion elsewhere and was subsequently diagnosed as dermatofibrosarcoma protuberans when the lesion recurred. Conclusion: A high index of clinical suspicion is warranted in the cases of slow growing plaques of nodules in trunk and extremities to avoid a delay in the diagnosis of dermatofibrosarcoma protuberans.